Strategy improving students' understanding of multiplication concepts through abacus props abacus 100 beads class 2 sd negeri 0119 banjar raja - Hasibuan, Muhammad Asyhari; Harahap, Nurhalimah; Mutiah, Era (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
Muhammad Asyhari Hasibuan. "Strategy to Increase Students' Understanding of the Concept of Multiplication Using a 100-Bead Abacus Teaching Aid for Class II SD Negeri 0119 Banjar Raja." Thesis, Madrasah Ibtidaiyah Teacher Education Study Program (PGMI). STAI Barumun Raya Sibuhuan. 2023. This research aims to determine (1) understanding of the concept of multiplication of class II students at SD Negeri 0119 Banjar Raja. (2) a strategy to increase students' understanding of the concept of multiplication using a 100-bead abacus teaching aid for class II SD Negeri 0119 Banjar Raja. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out in class II of SD Negeri 0119 Banjar Raja. The data sources in this research were divided into two, namely (1) primary data from class II students at SD Negeri 0119 Banjar Raja, (2) secondary data, namely class II teachers at SD Negeri 0119 Banjar Raja. . Data collection techniques in this research were obtained through interviews, observation, written tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the research results, it can be concluded that (1) The understanding of the concept of multiplication of class II students at SD Negeri 0119 Banjar Raja is still below the KKM, it can be seen that 1 student or 6.67% has a "very good" understanding of the concept of multiplication. 2 students or 13.33 % understanding of concepts in multiplication "good", 3 students or 20.00% understanding of concepts in multiplication "fair", 8 students or 53.33% understanding of concepts in multiplication "Poor", 1 student or 6.67% understanding of concepts in multiplication "very less". (2) After using the 100-bead abacus teaching aid, students' understanding of the concept of multiplication in cycle I has begun to increase, namely 4 students or 26.67% who have a "very good" understanding of the concept of multiplication. 9 students or 60.00% understand the concept of multiplication." good”, 1 student or 13.33% understand the concept in multiplication “fairly”, there are no students understanding the concept in multiplication “Not enough”, there are no students understanding the concept in multiplication “very poor”. The second cycle students' understanding of the concept of multiplication has increased, namely 12 students or 80.00% who have a "very good" understanding of the concept in multiplication. 3 students or 20.00% have a "good" understanding of the concept in multiplication, no understanding of the concept in "fair" multiplication. , there are no students who understand the concept of multiplication "Not enough", there are no students who understand the concept of multiplication "very less".Keywords: Mastery Learning Learning Model, Student Learning Outcomes